2020
DOI: 10.1097/ico.0000000000002458
|View full text |Cite
|
Sign up to set email alerts
|

Scheimpflug Densitometry in Keratoconus: A New Method of Visualizing the Cone

Abstract: Purpose: To report an observation made while performing Scheimpflug densitometry analysis on the corneal region affected in keratoconus (KC) that seems to delineate the base of the cone. Methods: Scheimpflug densitometries of 20 healthy subjects and 90 patients with KC were examined. Corneal densitometry was analyzed using both “1-layer” and “2-layer” approaches. The first considers the corneal transparency layer by layer at different depths, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The 'one-layer' and 'two-layers' scan method to obtain the images was reported in a previous study. 11 'Two-layers' scans of 50 patients constitute the map set subject to analysis. For the purposes of consistency, Layer 1 was always chosen as the first value ≥120 µm (i.e., excluding epithelium, Bowman's layer and anterior stroma) and the endothelium was chosen as Layer 2.…”
Section: Densitometry Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The 'one-layer' and 'two-layers' scan method to obtain the images was reported in a previous study. 11 'Two-layers' scans of 50 patients constitute the map set subject to analysis. For the purposes of consistency, Layer 1 was always chosen as the first value ≥120 µm (i.e., excluding epithelium, Bowman's layer and anterior stroma) and the endothelium was chosen as Layer 2.…”
Section: Densitometry Analysismentioning
confidence: 99%
“…[7][8][9][10] We recently reported an observation that appears to delineate the cone in KC based on densitometry marks seen on Scheimpflug tomography. 11 The major advantage of the bright densitometry marks over classical tomographic maps is that it relies only on the light's transmission properties. While the classical maps are founded on calculations and assumptions, densitometry maps are based on raw data, and therefore no assumptions about corneal refractive index, geometrical optics, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Recently, and in agreement with the findings of Lopes et al, 13 our group reported that densitometry might be used to accurately demarcate the location of clinical keratoconus. 14 One of the major drawbacks of densitometry, however, is that, to date, it is exclusively available on one single commercial device. To overcome this limitation, our research group introduced densitometry distribution analysis (DDA), 15 which is a platform-independent methodology based on the statistical modeling of the pixel intensity distribution of Scheimpflug images that correlates very well with traditional densitometry (overall cornea, r = 0.89; P < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Keratoconus (KC) is a progressive, ectatic corneal disorder presenting with central or paracentral stromal thinning associated, among others, with corneal protrusion, structural changes, and transparency loss [ 1 , 2 , 3 ]. The condition has a multifactorial etiology, attributable to a genetic predisposition, eye rubbing, or biomechanical factors [ 4 ], and a cascade of biomechanical decompensation triggered by a focal change in corneal elasticity is thought to be responsible for KC progression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%